(untitled) (Pain medicine, 2020)
The article reflects the current position of the issue of morphologies of the pathways of intercellular circulation in the brain. There are covered main, known at present time, data on the features of the exchange between the spinal fluid and intercellular fluid, the ways of elimination of the intertissued fluid of the brain through the so-called “glymphatic system”, its components: transarterial, transvenous, and transglial ways of intercellular fluid outflow from brain tissue. It also raises the question of the role of glia namely astrocytes and ependymocytes – as the main cells forming the haemato-encephalic barrier and participating in the intercellular circulation.